Comparison of nickel, cobalt, pelladium and tungsten schottky contacts on n-4H-SiC - Gora, V. E; Nyamhere, C.; Chawanda, Albert; Auret, F.D.; Mazunga, Felix; Jaure, T.; Chibaya, Blessing; Omotoso, Ezekiel; Danga, Helga; Tunhuma, Shandirai Malven (Elsevier, 2018)
We have investigated the current-voltage (I-V) characteristics of nickel (Ni), cobalt (Co), tungsten (W) and palladium (Pd) Schottky contacts on n-type 4H-SiC in the 300–800 K temperature range. Results extracted from I-V measurements of Schottky barrier diodes showed that barrier height (ФBo) and ideality factor (n) were strongly dependent on temperature. Schottky barrier heights for contacts of all the metals showed an increase with temperature between 300 K and 800 K. This was attributed to barrier inhomogeneities at the interface between the metal and the semiconductor, which resulted in a distribution of barrier heights at the interface. Ideality factors of Ni, Co and Pd decreased from 1.6 to 1.0 and for W the ideality factor decreased from 1.1 to 1.0 when the temperature was increased from 300 K to 800 K respectively. The device parameters were compared to assess advantages and disadvantages of the metals for envisaged applications.